Intercultural Communication of Foreign Students at UIN Mahmud Yunus Batusangkar - Syafriwaldi Syafriwaldi; Zainal Fadri; Azhari Maulana; Andhika Gilang Prayoga (Alfuad: Jurnal Sosial Keagamaan, 2022)
The problem in this study is the process of intercultural communication that occurs in foreign students at UIN Mahmud Yunus Batusangkar between students from Thailand, Cambodia, Malaysia and Minangkabau students while at UIN Mahmud Yunus Batusangkar. This study looks at the point of view of verbal and non-verbal communication as well as various supporting and inhibiting factors in the daily life of foreign students at UIN Mahmud Yunus Batusangkar by using field research (Field Research) which is descriptive qualitative. The results obtained are that at least foreign students have cultural similarities because they are still in the same clump, namely the Malay family in Southeast Asia, the greetings done by Thais and Cambodians tend to wait for greetings from other people, while Malaysians and Indonesians - Minangkabau tend to be friendly and polite. precede the conversation when communicating and greeting. Meanwhile, Minangkabau students use a pattern of adjustment by blurring cultural identity, reducing stereotypes and high openness. The supporting factors for this research are positive values, such as being a student who is tolerant and harmonious with each other, while the inhibiting factor is language.